2022
DOI: 10.1002/clc.23928
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of global longitudinal strain in hypertrophic cardiomyopathy: A systematic review and meta‐analysis

Abstract: Background As previously reported, impairment of left ventricular global longitudinal strain (LVGLS) is associated with myocardial fibrosis, arrhythmias, and heart failure in hypertrophic cardiomyopathy (HCM) patients. Hypothesis This study aimed to estimate the association between LVGLS measured by echocardiography and major adverse cardiovascular events (MACE) in patients with HCM. Methods Pubmed, Embase, Scopus, and Cochrane Library databases were systematically searched for evaluating the difference of LVG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…32 A meta-analysis that included 2441 patients confirmed the role of global longitudinal strain in predicting the outcome and risk stratification of HCM patients. 33 Even after septal myectomy, global longitudinal strain predicted worse survival rates;…”
Section: Discussionmentioning
confidence: 99%
“…32 A meta-analysis that included 2441 patients confirmed the role of global longitudinal strain in predicting the outcome and risk stratification of HCM patients. 33 Even after septal myectomy, global longitudinal strain predicted worse survival rates;…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up duration extended for a period of 6 months, during which no attrition of clinical patients occurred. Throughout this follow-up period, the incidence of major adverse cardiovascular events (MACE) [11] was diligently recorded among AMI patients. Subsequently, patients were categorized into two distinct groups, namely the MACE group and the non-MACE group, based on the occurrence of these adverse events.…”
Section: Follow-upmentioning
confidence: 99%
“…GLS has been used as an early marker of systolic dysfunction in genotype-positive phenotype-negative patients. It carries incremental prognostic value, being associated with adverse outcomes and progression to heart failure [37,38]. Moreover, pediatric studies on myocardial torsion have demonstrated an abnormal basal rotation with preserved or increased apical rotation [39].…”
Section: Echocardiography Application To Paediatric Cardiomyopathiesmentioning
confidence: 99%